A APRENDIZAGEM SOCIOAMBIENTAL DOS VISITANTES EM UNIDADES DE CONSERVAÇÃO - Machado, Bernadete (2008)
This investigation had an object of study: the socioambiental apprenticeship of a visitor from the perception of the environment looking into the interpretative trails (IT) from a preservation unit (PU). The actual research had theoretical Assumptions that are to basal the arguments, the studies proposed By Piaget regarding the construction of the knowledge. The questions that this study tries to answer are related to: what contributions the visit to an Environmental protected area can bring out about the feasibility of the socioambiental apprenticeship of the visitors? What kind of situations the experience of the visitors can contribute to provide the acquisition of socioambiental attitudes; How the interaction of the visitors with the environment, can bring cognitive disequilibriums able to promote the socioambiental apprenticeship? The objectives from the actual research are: to investigate the factors that promote the perception of the visitors into an IT, they can implicate on the socioambiental apprenticeship; to describe situations into the IT, that can contribute for the visitors to develop socioambientals attitudes from the visit of an environmental protective area; and, also, to analyze moments where the perception of the visitors produces a cognitive disequilibrium. The research was developed from the analysis of the auto guided tracks and interpretative trails, both from the Guartelá State Park (GEP), in Tibagi City in the Paraná State. The guys from this research were the individuals who visited the preservation unit (UP) in the period of February, and also, from May to August in the year of 2008. It treats a qualitative research with a methodology that involves an interface of the research-action with the ethnographic research type. We use as procedures the collection of information: a questionnaire quasi-structured, handled to the visitors in an exploratory intervention with the purpose to trace the relevance of the visit into a PU; the interview not directive directioned to the visitors in the course of the trails; aside from, the observation with self itinerary. We present as result the educational potentiality of an IT. And about the guys, was expressed that the individuals who showed themselves more sensitive with the environment also did not surpassed the centerboard in the process of construction of the knowledge. About the guys who found problems in the characteristics of the environment showed an uncentreboard effort. With this investigation was possible to conclude that the activities promoted during the interventions, showed the perception of the visitor in the IT. The cognitive disequilibrium presented by a few guys has led them to be more liable to the apprenticeship.